Rubber composition for vehicle tire inner liner
The airtightness and crack resistance of tire lining are solved by using specific combinations of rubber compositions and HTC lignin fillers in pneumatic tire linings, combining zinc oxide and sulfur vulcanization systems, achieving low density and high efficiency tire performance.
Patent Information
- Application Number
- CN202180008044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-23
- Filing Date
- 2021-09-22
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-09-22
AI Technical Summary
The prior art has failed to effectively provide an environmentally friendly rubber composition suitable for pneumatic tire linings, especially in terms of airtightness and crack resistance, and the rubber composition containing carbon black is of high density, affecting tire performance.
A rubber composition comprising a selected group consisting of bromobutyl rubber and chlorobutyl rubber and using HTC lignin with a specific 14C content, carbon content and surface acidic hydroxyl groups as filler, combined with zinc oxide and sulfur to form a vulcanization system. Vulcanizable rubber compositions to improve the performance of the lining.
The low density, high airtightness and good crack resistance of the lining are achieved, the rolling resistance of the tire is reduced, the fuel efficiency and environmental friendliness are improved, and the use of fossil energy is avoided.
Smart Images

Figure BDA0003727637450000261 
Figure BDA0003727637450000281
Abstract
Description
Technical Field
[0001] The present invention relates to rubber compositions, more particularly to vulcanizable and vulcanized rubber compositions for innerliners of pneumatic vehicle tires. The invention also relates to a kit of parts for making the composition, and to methods for making and further processing the composition, and to methods for making pneumatic tires. The invention also relates to the use of special fillers made from recycled raw materials for the preparation of rubber compositions, in particular for innerliners. Background Art
[0002] Pneumatic vehicle tires have a complex construction. The requirements placed on them are accordingly varied. On the one hand, short braking distances must be ensured on both dry and wet roads, and on the other hand, they must have good wear resistance and low rolling resistance. In addition, vehicle tires must comply with legislative requirements.
[0003] To ensure this diverse performance, the individual tire components are specially designed and consist of a variety of different materials such as metal, polymer textile materials and various rubber-based components.
[0004] Depending on the design of the pneumatic tire, a distinction is made between radial tires, cross-ply tires and bias-ply tires or belted bias tires. A typical pneumatic tire (as an example of a radial-ply belted tire) comprises at least a belt, a belt cover, a tread, a reinforcing belt, a sidewall, a bead filler, a bead wire, an inner liner and a carcass.
[0005] The belt is usually made up of multiple layers of twisted steel wires that are coated with rubber and arranged at angles. Its main purpose is to provide structural strength to the tire in its inflated state. The belt also provides driving stability during acceleration, braking and cornering. It affects rolling resistance and significantly increases the mileage of the tire.
[0006] The belt cover between the tread and the upper belt is used to improve high-speed performance and limit the tire diameter at high speeds.
[0007] The tread plays a crucial role in driving characteristics. The rubber compound of the tread determines the wear characteristics and dynamic driving characteristics in different weather conditions (on wet and dry roads, in cold and warm weather, on ice and snow). In turn, the design of the tread pattern largely determines the tire's performance in hydroplaning and wet conditions and on snow, and also determines its noise performance.
[0008] Optionally, a reinforcing tape is used in the bead filler area to further improve tire strength and ride characteristics.
[0009] The sidewalls protect the carcass from lateral damage and environmental influences. The rubber compound used for the sidewalls is elastic and wear-resistant and contains a relatively large amount of aggregate to protect against aging and ozone.
[0010] The bead filler sits on the bead wire / bead core. Its shape and configuration provide driving stability and have an influence on steering precision and suspension comfort. The rubber compounds used for bead fillers are usually very strong and relatively stiff, which is ensured by a high degree of crosslinking using a high-dose vulcanization system and by the choice of filler.
[0011] The bead wire is the inner part of the tire bead and consists of a twisted steel wire coated with rubber, which is wound in a toroidal shape and holds the tire stably on the rim. In the common tubeless configuration, the bead (also called the tire base or tire foot) is pressed against the rim flange and closes the tire in an airtight manner. The steel cords and wires in the bead core, tread or carcass of an all-steel tire must be firmly connected to the surrounding rubber compound to function as a composite material. For this purpose, the steel wire is usually coated with brass or bronze. Only after this, the steel wire bonding compound is used to form these components, which are then assembled to form the tire blank. Due to its high proportion of natural rubber, the steel wire bonding compound has a relatively strong tear resistance, for example through special resin additives and a high sulfur content with a brass or bronze coating to achieve a strong connection. The permanent connection is formed during the vulcanization process.
[0012] The carcass forms the basic structure of the tire and consists of one or more fabric layers (rayon, nylon, polyester, aramid) or layers of steel cords embedded in rubber (for trucks). The carcass is subjected to tension by the tire air pressure and is therefore essentially responsible for the transmission of forces between the rim and the tread / street. It is connected to the beads in the tire base, thus holding the tire together. The carcass functions as a composite between the cord layers and the rubber compound that wraps the parallel cords, which ensures strength and force transmission. Since the tire is constantly deforming, the cord compound must be fatigue-resistant, which is usually achieved by a blend of natural and synthetic rubber, and it must also form a strong connection with the cords. To this end, the cords are coated with a rubber compound after twisting / winding. The cords with this finish are coated with an unvulcanized rubber compound. The resin system in the special compound then reacts with the cord finish during the vulcanization process to form a durable composite material.
[0013] As mentioned above, modern tires are usually tubeless. The so-called inner liner is a layer of rubber compound that is arranged radially inwards and is as airtight as possible. It is also called the inner core or inner plate and serves to ensure that the air pumped into the tire cannot escape over a long period of time, as the air pressure significantly influences the driving characteristics and durability of the tire. In addition, the internal pressure also affects the rolling resistance of the tire. Reduced air pressure leads to greater dynamic deformation of the tire, which in turn results in part of the kinetic energy being converted into heat energy unnecessarily. This has a negative impact on the vehicle's fuel consumption and therefore on the associated CO2 emissions.
[0014] In addition, the liner protects the carcass from the diffusion of air and moisture therein and prevents any damage to the carcass and / or the strength-providing elements of the belt. In order to keep the liner as airtight as possible, the liner should also have good tear and fatigue resistance so that no tears that affect airtightness occur during driving.
[0015] Due to this specific requirement, the composition of the rubber compounds for innerliners is quite different from that of the rubber compounds for other tire parts, both in terms of the rubbers and fillers used and the weight ratios between the components, but they still need to be compatible with the adjacent tire parts and, in particular, have good adhesion to these parts. In addition to the type of rubber, the minimum amount of different rubbers in the rubber compound also plays a role, as do the various specific parameters and properties of the fillers that can be used.
[0016] Among them, halogenated butyl rubber (such as chlorobutyl rubber or bromobutyl rubber) is occasionally blended with other rubbers and used as lining rubber. Butyl and halogenated butyl rubbers have low gas permeability. Halogenated butyl rubber is blended with other rubbers (such as natural rubber) to increase viscosity, reduce costs and adjust mechanical properties during assembly.
[0017] The gas tightness of the inner liner can be further increased by the addition of large amounts of low-activity or inactive fillers to the rubber compound of the inner liner. The fillers used to date include, in particular, furnace carbon black.
[0018] To prevent crack formation under dynamic loads, the liner must have a balanced elastic modulus and matching hardness, which is usually in conflict with a high proportion of inactive fillers. Therefore, mineral oil-based softeners are usually added to the rubber composition, which reduces the elastic modulus and hardness of the composition, but at the same time increases the gas permeability, resulting in a relatively narrow range of the optimal amount of mineral oil-based softeners and fillers used.
[0019] In addition, many fillers, such as N 660 carbon black, have a density of about 1.8 g / cm 3The relatively high density of the filler is above 100%. Therefore, the rubber composition compounded with such fillers also has a higher density and thus has a higher weight for the same volume. However, the higher the density of the filler, the heavier the inner liner is, and ultimately the heavier the pneumatic tire is, which in turn leads to higher fuel consumption.
[0020] Furthermore, industrial carbon black is produced petrochemically by incomplete combustion or pyrolysis of hydrocarbons. However, from an environmental point of view, the use of fossil energy for the production of fillers must be avoided or minimized. Instead, the goal should be to provide fillers for compounding based on biomass and that meet the multiple requirements of liner.
[0021] In the field of the preparation of rubber compositions generally used for tires, WO 2017 / 085278 A1 discloses the use of so-called HTC lignin, which is lignin converted by hydrothermal carbonization, as a filler to replace industrial carbon black.
[0022] Lignins are solid biopolymers that are incorporated into plant cell walls, thus affecting the lignification of plant cells. Therefore, they are contained in biorenewable raw materials and, in hydrothermal carbonized form, have the potential to be an environmentally friendly alternative to industrial carbon black in rubber compositions.
[0023] However, the prior art does not clearly describe the use of such fillers in special rubber compositions, such as compositions for innerlinings, especially because possible interactions between the innerlining rubber (which usually carries reactive atoms) and the reactive surface groups of HTC lignin are not known and the properties of the resulting vulcanizates have not been thoroughly investigated.
[0024] WO 2017 / 194346 A1 also describes the use of HTC lignin in rubber compounds for pneumatic tire components, in particular for use with methylene donor compounds (e.g., hexa(methoxymethyl)melamine) to increase the stiffness of cured rubber components of pneumatic tires, as well as to replace phenolic resins and / or in combination with silane coupling agents. One of the purposes addressed in WO 2017 / 194346 is to reduce the rolling resistance of the tire. Natural rubber, polybutadiene rubber, styrene-butadiene rubber and polyisoprene rubber are specified as suitable rubber materials. WO 2017 / 194346A1 discloses the suitability of the rubber compound described therein for the tread area, sidewalls and beads of pneumatic tires. A rubber compound that meets the requirements for the inner liner is not described.
[0025] EP 3 470 457 A1 also discloses a vulcanizable sulfur-containing rubber compound for vehicle tires. The filler used for testing solvent polymerized styrene-butadiene rubber (SSBR) is HTC coal, which is obtained from various raw materials, produced by adding metal halides, and shows a BET surface area of up to more than 180 m 2 / g. Among them, the BET surface area was found to be 90m 2 / g to 140m 2 HTCs of 0.1 Å / g are particularly preferred because they are believed to have enhanced surface roughness and optimized surface functionality.
[0026] Therefore, from the overall perspective of the prior art, there is a particular need for a rubber composition or rubber compound suitable for pneumatic tire innerliners, which contains an environmentally friendly material alternative to carbon black based on recycled raw materials as a filler, and provides a vulcanized rubber composition that meets the requirements of pneumatic tire innerliners, especially in terms of air tightness and crack resistance, and preferably has a lower density than a rubber composition containing carbon black, as well as good tear resistance and tear propagation resistance. Summary of the invention
[0027] The problem involved in the present invention can be solved by providing a rubber composition comprising:
[0028] The rubber component
[0029] comprising at least one halogenated butyl rubber selected from the group consisting of bromobutyl rubber and chlorobutyl rubber,
[0030] Filler ingredients, the filler ingredients
[0031] Contains at least one filler F1, which
[0032] 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon;
[0033] The carbon content is in the range of 60% to 85% by weight relative to the ash-free and water-free filler;
[0034] STSA surface area in 10m 2 / g filler up to 50m 2 / g filler range;
[0035] and
[0036] Having acidic hydroxyl groups on its surface;
[0037] And wherein the ratio of the halogenated butyl rubber in the rubber composition is 70 phr to 100 phr.
[0038] The phr (parts per hundred parts of rubber by weight) specification used herein is a quantity specification commonly used in the rubber industry for compound formulations. The dosage of each component in parts by weight is always based on 100 parts by weight of the total mass of all rubbers present in the compound.
[0039] This rubber composition will also be referred to hereinafter as the rubber composition of the present invention or the rubber composition according to the present invention.
[0040] The present invention also relates to a vulcanizable rubber composition, which comprises or consists of the rubber composition of the present invention and a vulcanization system containing zinc oxide and / or sulfur.
[0041] This vulcanizable rubber composition will also be referred to hereinafter as the vulcanizable rubber composition of the present invention or the vulcanizable rubber composition according to the present invention.
[0042] Another object of the invention is a kit which comprises the rubber composition of the invention and a vulcanization system containing zinc oxide and / or sulfur in spatially separated form.
[0043] This kit will also be referred to hereinafter as the inventive kit or the kit according to the invention.
[0044] Another object of the present invention is a process for preparing the rubber composition of the invention and the vulcanizable rubber composition of the invention, the latter being obtained by preparing the rubber composition of the invention as a base compound (masterbatch) by compounding the components of the rubber composition in a first stage and by mixing the components of the vulcanization system in a second stage.
[0045] These methods will also be referred to as methods of the present invention for preparing the rubber composition of the present invention or the vulcanizable rubber composition of the present invention.
[0046] Another object of the present invention is a process for further processing the vulcanizable rubber compositions of the invention, in which they are formed into webs by calendering, extrusion or the so-called roller-head process.
[0047] This method will also be referred to as method of further processing according to the invention or method of further processing according to the invention.
[0048] Another object of the invention is a method for manufacturing a pneumatic tire, comprising the method of further processing according to the invention, and a subsequent step of cutting the web obtained into dimensions suitable for an innerliner of a pneumatic tire, and comprising a subsequent step of vulcanizing the innerliner thus obtained, preferably together with a pneumatic tire carcass.
[0049] This method will also be referred to as a method for manufacturing a pneumatic tire of the present invention or a method for manufacturing a pneumatic tire according to the present invention.
[0050] Another object of the present invention is the use of a filler as characterized above, which is suitable in the context of the present invention for preparing a rubber composition for an inner liner.
[0051] This use will also be referred to as use of the invention or use according to the invention. DETAILED DESCRIPTION
[0052] Hereinafter, each component of the rubber composition, the above-mentioned method and use, and particularly suitable process steps respectively used in the rubber composition will be described in detail.
[0053] Rubber composition
[0054] rubber
[0055] In the context of the present invention, one or more halogenated butyl rubbers selected from the group consisting of chlorobutyl rubber (CIIR; chloro-isobutylene-isoprene rubber) and bromobutyl rubber (BIIR; bromo-isobutylene-isoprene rubber) are used.
[0056] Halogenated butyl rubbers are halogenated isobutylene-isoprene rubbers. They can be obtained by halogenation, especially bromination and / or chlorination, of butyl rubber.
[0057] Butyl rubber is mainly composed of isobutylene units, and the rest is isoprene units. It is particularly preferred that the proportion of isobutylene units is 95 mol % to 99.5 mol %, the proportion of isoprene units is 0.5 mol % to 5 mol %, and it is more particularly preferred that the proportion of isobutylene units is 97 mol % to 99.2 mol % and the proportion of isoprene units is 0.8 mol % to 3 mol %, wherein the proportion of isobutylene units and isoprene units preferably totals 100 mol % of the monomers contained therein and polymerized into the polymer. Butyl rubber generally has a low gas and water permeability.
[0058] Due to the isoprene units polymerized into the rubber, butyl rubber has carbon-carbon double bonds which are useful for both vulcanization and halogen (particularly chlorine and bromine) modification.
[0059] Halogenated butyl rubbers obtainable by halogen modification (halogenation) have a higher reactivity than butyl rubber and therefore a wider range of vulcanization possibilities, such as, in particular, the possibility of co-vulcanization with other rubbers such as natural rubber (NR), butyl rubber (IIR; isobutylene-isoprene rubber) and styrene-butadiene rubber (SBR).
[0060] Among the halogenated butyl rubbers, bromobutyl rubber is more reactive due to its weaker carbon-bromine bond compared to chlorobutyl rubber which has a carbon-chlorine bond, which provides a wider range of cure systems for bromobutyl rubber. Bromobutyl rubber cures faster and generally has better adhesion to diene rubbers.
[0061] Among the halogenated butyl rubbers, bromobutyl rubber is particularly preferred in the context of the present invention.
[0062] However, it is also possible to use a compound of one or more bromobutyl rubbers and one or more chlorobutyl rubbers as the halogenated butyl rubber component. Here, the bromobutyl rubber increases the vulcanization rate.
[0063] Suitable chlorobutyl rubbers (CIIR) in the context of the present invention preferably contain 1.1 to 1.3% by weight of chlorine, and bromobutyl rubbers (BIIR) preferably contain 1.9 to 2.1% by weight of bromine. This corresponds to a proportion of about 2 mol % of reactive sites.
[0064] The viscosity of the halogenated butyl rubber is preferably 35 to 55 Mooney units (ML (1+8), 125° C.). Like butyl rubber, the product contains virtually no secondary components (rubber ratio>98.5). The halogenated butyl rubber preferably contains a stabilizer, in particular a sterically hindered phenol as a stabilizer.
[0065] The rubber composition of the present invention may contain, in addition to the halogenated butyl rubber, one or more other rubbers than the halogenated butyl rubber.
[0066] Particularly preferred further rubbers other than halogenated butyl rubber, if present, are natural rubber, butyl rubber and styrene-butadiene rubber.
[0067] For example, by mixing natural rubber with halogenated butyl rubber, particularly compared with general-purpose rubber, it is possible to improve the adhesion with other rubber-based tire components. By cross-linking different rubbers, a synergistic effect can be produced in terms of tensile strength, making it even higher than the tensile strength of a single rubber. This is especially true when using the following vulcanization system, which comprises zinc oxide, sulfur and thiazole, such as mercaptobenzothiazole disulfide (MBTS). On the other hand, the gas and moisture permeability of the vulcanized final product increases with the mixing of natural rubber usually.
[0068] The mixing of styrene-butadiene rubber with halogenated butyl rubber can be carried out in the same manner as the mixing of natural rubber, but generally offers no particular advantages over natural rubber, so the use of natural rubber is generally preferred to the use of styrene-butadiene rubber.
[0069] Blending up to 30 phr, preferably up to 20 phr, of butyl rubber relative to the halogenated butyl rubber generally has little or no effect on the gas and moisture permeability of the cured final product, but it can, if desired, reduce the cure rate and increase heat resistance.
[0070] The total amount of halogenated butyl rubber is from 70 to 100 phr, preferably from 80 to 100 phr, particularly preferably from 90 to 100 phr, most preferably 100 phr.
[0071] In the case where the rubber compound contains less than 100 phr of halogenated butyl rubber, the rubber composition contains at least one other rubber, preferably one of the above-mentioned rubbers, so that the total amount of rubber contained is 100 phr.
[0072] This means that the amount of further rubber other than halogenated butyl rubber is from 0 phr to 30 phr, preferably from 0 phr to 20 phr, particularly preferably from 0 phr to 10 phr and very particularly preferably from 0 phr.
[0073] Filling F1
[0074] The mandatory filler component is filler F1, which
[0075] 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon, preferably 0.23 Bq / g carbon to 0.42 Bq / g carbon;
[0076] The carbon content is in the range of 60% to 85% by weight, preferably 63% to 80% by weight, particularly preferably 65% to 75% by weight, and very particularly preferably 68% to 73% by weight, relative to the ash-free and water-free filler;
[0077] STSA surface area in 10m 2 / g filler up to 50m 2 / g filler, preferably 15m 2 / g filler up to 45m 2 / g filler, particularly preferably 20m 2 / g filler up to 40m 2 / g filler;
[0078] And has acidic hydroxyl groups on its surface.
[0079] Such fillers F1 are referred to hereinafter as "fillers to be used according to the invention" or "fillers which can be used according to the invention" or "fillers used according to the invention".
[0080] The above required 14The C content is achieved by fillers obtained from biomass by further processing or reaction, preferably by decomposition, wherein the decomposition can be carried out thermally, chemically and / or biologically, preferably thermally and chemically. Therefore, fillers obtained from fossil materials (such as, in particular, fossil fuels) do not belong to the definition of fillers to be used according to the present invention, because they do not have the corresponding 14 C content.
[0081] In the present context, biomass is in principle defined as any biomass, wherein the term "biomass" in the present context includes so-called plant matter (i.e. biomass from plants), animal matter (i.e. biomass from animals) and microbial organisms (i.e. biomass from microorganisms including fungi), wherein biomass is dry biomass or fresh biomass, originating from dead or living organisms.
[0082] Particularly preferred biomass for preparing fillers herein is plant matter, preferably dead plant matter. Dead plant matter includes dead, discarded or dismantled plants and parts thereof. For example, these include broken and torn leaves, twigs, twigs and branches, fallen leaves, felled or pruned trees, as well as seeds, fruits and parts derived therefrom, but also sawdust, wood shavings / wood chips and other wood processing products.
[0083] The abovementioned carbon contents are usually obtained from fillers based on biomass decomposition and can be determined by elemental analysis in accordance with DIN 51732:2014-7.
[0084] Preferably, the oxygen content of the filler is in the range of 15% to 30% by weight, preferably 17% to 28% by weight, particularly preferably 20% to 25% by weight, relative to the ash-free and water-free filler. The oxygen content can be determined by high-temperature pyrolysis, for example using the EuroEA3000 CHNS-O analyzer from EuroVector SpA.
[0085] In addition, the filler of the type defined above has acidic hydroxyl groups (so-called surface available acidic hydroxyl groups) on its surface. The surface available acidic hydroxyl groups can be qualitatively and quantitatively determined by colorimetry according to Sipponen. The method according to Sipponen is based on the adsorption of basic dye Azure B on the available acidic hydroxyl groups on the filler surface. If there is corresponding adsorption under the conditions quoted in the article 2.9 (page 82) mentioned below, there are acidic surface available hydroxyl groups in the sense of the present invention. More details can be found in the paper "Determination of surface-accessible acidic hydroxyls and surface area of lignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87). When quantitatively determined, the amount of surface available acidic hydroxyl groups is expressed in mmol / g filler. Preferably, the amount of surface available acidic hydroxyl groups is in the range of 0.05mmol / g to 40mmol / g, particularly preferably 0.1mmol / g to 30mmol / g, and more particularly preferably 0.15 to 30mmol / g. Preferred surface available acidic hydroxyl groups are phenolic hydroxyl groups.
[0086] There is also a clear difference between the BET surface (total specific surface area according to Brunauer, Emmett and Teller) of biomass-based fillers and their external surface (STSA surface area; statistical thickness surface area).
[0087] For example, WO 2017 / 085278 A1 describes that the STSA surface area of hydrothermal carbonized lignin is 5 m 2 / g to 200m 2 / g range, hydrothermal carbonized lignin, i.e. fillers based on dead plant matter containing lignin obtained by hydrothermal treatment. In the experimental part of this disclosure, it is even mentioned that the surface area of STSA is only 2.6 m 2 / g of material.
[0088] Characterization of filler F1 14 All of the above ranges for C content, carbon and oxygen content, STSA surface area and surface available acidic groups apply equally to all fillers F1 to be used according to the invention, preferably lignin-based fillers, which here represent a preferred class of fillers preparable from plant materials.
[0089] In their textbook "Kautschuk Technologie-Werkstoffe Verarbeitung Produkte" (3rd revised and expanded edition 2013, pages 1196-1197), and Sommer divided the various rubbers into three categories: rubbers with low polarity and high oil swelling, rubbers with medium polarity and medium oil swelling, and rubbers with high polarity and low oil swelling. Although halogenated butyl rubber is reactive, its polarity is low.
[0090] The good compatibility of the fillers to be used according to the invention, in particular lignin-based fillers, with halogenated butyl rubbers, which have only a low polarity, is therefore particularly surprising, since the fillers to be used according to the invention have a high polarity compared to typical industrial carbon blacks, which is mainly due to the content of surface-available acidic hydroxyl groups, but also to the higher oxygen content compared to industrial carbon blacks.
[0091] Accordingly, among the lignin-based fillers, hydrothermally treated lignin-containing plant bodies are particularly preferred. The preferred treatment is a hydrothermal treatment carried out in the presence of liquid water at a temperature of 150°C to 250°C. Compared with the original lignin, the carbon content is generally increased and the oxygen content is reduced. Suitable treatment methods are described, for example, in WO 2017 / 085278A1. The lignin-based filler obtained by hydrothermal treatment is also referred to as HTC lignin below. The hydrothermal treatment carried out in the presence of liquid water in the temperature range of 150°C to 250°C is also referred to as hydrothermal carbonization hereinafter. The HTC lignin described below is a preferred filler used in the context of the present invention.
[0092] The rubber composition of the present invention preferably comprises 50 to 100 phr, particularly preferably 55 to 85 phr, more particularly preferably 60 to 80 phr, for example 65 to 75 phr of the filler to be used in the present invention as defined above. If a filler with a higher STSA surface area range as defined in the present invention is used, its amount may be reduced, resulting in an inner liner with a lower weight and reinforcement properties due to the STSA surface area. If a filler with a lower STSA surface area as defined in the present invention is used, the amount of filler can be significantly increased, thereby reducing gas permeation and improving tear resistance. The reinforcement properties are then not up to the level of a rubber composition reinforced with a filler with a higher STSA surface area.
[0093] HTC lignin
[0094] HTC lignin is obtained by hydrothermal carbonization of a lignin-containing raw material and represents a particularly preferred filler F1 that can be used according to the invention. The properties of HTC lignin can vary within a wide range. For example, different HTC lignins differ in their BET and STSA surface areas, ash content, pH and heat loss as well as density and particle size and the amount of acidic hydroxyl groups available on the surface.
[0095] In the context of the present invention, the special HTC lignin as filler to be used in the present invention is used as a substitute material for the carbon black usually contained in the rubber composition for inner liner. For example, WO 2017 / 085278A1 describes the preparation of HTC lignin that can be used in the present invention.
[0096] Although the above-mentioned documents WO 2017 / 085278 A1 and WO 2017 / 194346 A1 generally mention the use of HTC lignin as a possible alternative material to carbon black in tires, it should not be concluded that the behavior of HTC lignin in ordinary rubber compositions is easily transferred to the special rubber composition of the present invention, which contains more active halogenated butyl rubber. This is especially true for their use in rubber compositions based on halogenated butyl rubber, because they have completely different properties from ordinary rubber compositions, and due to the high reactivity of halogen atoms, especially chlorine atoms and especially bromine atoms, interactions and even reactions with fillers (especially HTC lignin) that can be used according to the present invention must be expected, because compared with industrial carbon black, the filler has a different chemical surface and composition. In particular, the difference in surface available acidic hydroxyl groups (preferably phenolic hydroxyl groups) between the above-mentioned industrial carbon black and the filler to be used in the present invention leads to surprisingly good miscibility of the filler and compatibility of the filler with the rubber component, even if no compatibilizer is used, especially no silane compound is used in the rubber composition of the present invention. The resulting vulcanizate has surprisingly good properties, wherein even critical properties such as the very low gas permeability required for inner liners are improved.
[0097] Therefore, the present invention requires the purposeful selection of special fillers. Among them, HTC lignin has been proven to be particularly suitable because they have excellent compatibility with other components of the rubber composition and with the special vulcanization system described below, and are particularly capable of achieving the required gas barrier properties and preventing tear formation and tear propagation.
[0098] The fillers to be used in the present invention, in particular the HTC lignin used in the present invention, are able to adjust a good balance of different properties in their use in inner liners. Thus, they have good reinforcing properties (expressed in stress values and tear strength), very high elongation at break, and they also promote good dispersion of the filler particles in the rubber.
[0099] To achieve this, it is advantageous if, in addition to the above-mentioned STSA surface area, the filler (preferably HTC lignin) used in the context of the present invention has a BET surface area of 15 g / m 2 Up to 50g / m 2 In the range of 18g / m 2 Up to 45g / m 2 , particularly preferably 20g / m 2 Up to 40g / m 2 .
[0100] Preferably, the filler used in the present invention (preferably HTC lignin) has a pH of >7 and <9, particularly preferably >7.5 and <8.5.
[0101] It was also found that the ash content and heat losses have only a small effect as long as the values are not too high, so as not to excessively reduce the content of active ingredients.
[0102] As shown in the experimental part of this application, the filler used herein (preferably HTC lignin) has the potential to completely replace carbon black in the preparation of rubber compositions, especially rubber compositions for producing innerliners. This means that the preferred rubber compositions of the present invention do not need to contain carbon black from fossil-derived materials.
[0103] This makes it possible, among other things, to produce innerliners for pneumatic tires having significantly lower weight, better air retention and better crack resistance, with the same dimensions as comparable innerliners obtained using carbon black. In particular, the better air retention ensures that the rolling resistance of the tire remains at an optimal level for a long time, thus enabling vehicles equipped with such tires to run more economically.
[0104] However, it is also possible to replace only a portion of the carbon black from fossil origin materials with one or more fillers usable according to the invention, preferably HTC lignin. The benefits are still significant, but to a lesser extent.
[0105] Other components of the rubber composition
[0106] Other fillers F2
[0107] Besides the above-mentioned filler F1 to be used according to the invention, preferably HTC lignin F1, the rubber composition may comprise other fillers F2 different from F1.
[0108] In the case where the filler F1 to be used according to the invention, preferably HTC lignin F1, is only a partial replacement for conventional industrial carbon black, the rubber composition of the invention may also comprise industrial carbon black, in particular furnace black classified as general purpose carbon black according to ASTM code N660.
[0109] Among the possible fillers, F2 are in particular inorganic fillers with different particle sizes, particle surface areas and chemical properties, which have different potentials for influencing the vulcanization behavior. In the case of the inclusion of other fillers, these should preferably have properties as similar as possible to the filler F1 (in particular HTC lignin) used in the rubber composition of the present invention, especially its pH value.
[0110] If other fillers F2 are used, they are preferably: phyllosilicates, such as clay minerals, for example talc; carbonates, such as calcium carbonate; silicates, such as calcium, magnesium and aluminum silicates; and oxides, such as magnesium oxide and silicon dioxide. However, in the context of the present invention, zinc oxide does not belong to fillers, since zinc oxide here performs the task of a vulcanizing agent. However, other fillers must be selected with care, since a high content of magnesium oxide, for example, can have a negative impact on the adhesion of adjacent tire layers, while silicon dioxide tends to bind organic molecules (such as thiazoles used in some vulcanization systems) to its surface, thereby inhibiting their action.
[0111] Inorganic filler, wherein preferred surface has silicon dioxide and other fillers of Si-OH group, also can carry out surface treatment.Particularly, may be favourable with the silylation of organosilane (for example alkyl alkoxy silane or aminoalkyl alkoxy silane or mercaptoalkyl alkoxy silane).Alkoxysilane group for example can be attached to the surface of silicate or silicon dioxide by hydrolysis condensation, or be attached to other suitable groups, and amino group and mercapto group for example can react with the halogenation (particularly bromination) isoprene unit of halogenated butyl rubber.This can cause the mechanical reinforcement of vulcanized rubber composition of the present invention.
[0112] The use of silanized fillers can accelerate the final state of cure and improve edge tear resistance.
[0113] The fillers may be used alone or in combination.
[0114] Preferably, no other fillers F2 are used in addition to the fillers F1 used according to the invention, in particular HTC lignin F1. If other fillers F2 are used, they are preferably industrial carbon black, in particular furnace black. However, among other fillers F2, in particular phyllosilicates, such as clay minerals, for example talc, are preferred.
[0115] When further fillers F2 are used, their proportion is preferably less than 40 phr, particularly preferably from 20 phr to 40 phr, particularly preferably from 25 phr to 35 phr.
[0116] softener
[0117] The use of softeners may affect the properties of the unvulcanized rubber composition, such as in particular the processability, and may also affect the properties of the vulcanized rubber composition, such as its flexibility, in particular at low temperatures.
[0118] Particularly suitable softeners in the context of the present invention are mineral oils from the group of paraffinic oils (essentially saturated chain hydrocarbons) and naphthenic oils (essentially saturated cyclic hydrocarbons). The use of aromatic hydrocarbon oils is possible, but less advantageous, because of their poor solubility with halogenated butyl rubber. However, with regard to the adhesion of the rubber composition to other rubber-containing components in the tire (e.g., the carcass), a mixture of paraffinic oils and / or naphthenic oils may be advantageous as a softener.
[0119] Other softeners are, for example, esters of aliphatic dicarboxylic acids, such as adipic acid or sebacic acid, paraffin waxes and polyethylene waxes.
[0120] Among the softeners, paraffinic and naphthenic oils are particularly suitable in the context of the present invention.
[0121] Preferably, softeners, more particularly preferably paraffin and / or naphthenic oils, are used in an amount of 0 to 15 phr, preferably 5 to 15 phr, particularly preferably 7 to 13 phr.
[0122] Adhesion enhancing resins (“tackifying resins”)
[0123] So-called adhesion-enhancing resins can be used to improve the adhesion of the cured rubber compounds of the present invention to other adjacent tire components.
[0124] Particularly suitable resins are phenol-based resins, preferably from the group consisting of phenol-formaldehyde resins, phenol-formaldehyde resins and phenol-acetylene resins.
[0125] In addition to phenol-based resins, aliphatic hydrocarbon resins, such as ExxonMobil's EscorezTM 1102RM, and aromatic hydrocarbon resins can also be used. Aliphatic hydrocarbon resins particularly improve adhesion to other rubber components of the tire. They generally have lower adhesion than phenol-based resins and can be used alone or as a mixture with phenol-based resins.
[0126] If an adhesion enhancing resin is used, it is preferably a resin selected from the group consisting of phenol-based resins, aromatic hydrocarbon resins and aliphatic hydrocarbon resins. Preferably, its proportion is 0 to 15 phr or 1 to 15 phr, particularly preferably 2 to 10 phr, and more particularly preferably 3 to 8 phr.
[0127] Additives to promote vulcanization
[0128] Rubber composition of the present invention can also include additives that promote vulcanization but can not start vulcanization voluntarily.Such additives include for example vulcanization accelerators, for example saturated fatty acids with 12 to 24, preferably 14 to 20 and particularly preferably 16 to 18 carbon atoms, such as zinc salts of stearic acid and aforementioned fatty acids.Thiazoles also can belong to these additives.However, it is also possible to use vulcanization accelerating additives only in the following vulcanization systems.
[0129] If vulcanization accelerating additives are used in the rubber composition of the invention, in particular the above-mentioned fatty acids and / or their zinc salts, preferably stearic acid and / or zinc stearate, their proportion is preferably 0 to 5 phr, particularly preferably 0.5 to 3 phr, particularly preferably 1 to 2 phr.
[0130] It is preferred that the rubber composition of the present invention thus contains, in addition to the essential ingredients, one or more ingredients selected from the group consisting of:
[0131] i. Rubber other than halogenated butyl rubber,
[0132] ii. a filler F2 different from the filler F1 to be used in the present invention,
[0133] iii. Softener,
[0134] iv. adhesion enhancing resins, and
[0135] v. Additives that promote vulcanization,
[0136] If it contains one or more of the ingredients listed in items i to v above, then
[0137] i. preferably a rubber selected from the group consisting of natural rubber, butyl rubber and styrene-butadiene rubber,
[0138] ii. a filler F2 preferably selected from the group consisting of carbon black and layered silicates,
[0139] iii. preferably esters of aliphatic dicarboxylic acids, paraffin oils and / or naphthenic oils,
[0140] iv. a resin selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins and phenol acetylene resins; and
[0141] v. is an additive selected from the group consisting of saturated fatty acids having 12 to 24 carbon atoms and thiazole.
[0142] If ingredients i to v are included, they are preferably included in the following amounts:
[0143] i. 0 phr to 30 phr, particularly preferably 0 phr to 20 phr, more particularly preferably 0 phr to 10 phr or 0 phr;
[0144] ii. 0 to 40 phr, particularly preferably 20 to 40 phr, more particularly preferably 25 to 35 phr,
[0145] iii. 0 to 15 phr, particularly preferably 5 to 15 phr, more particularly preferably 7 to 13 phr;
[0146] iv. 0 to 15 phr, particularly preferably 2 to 10 phr, more particularly preferably 3 to 8 phr; and
[0147] v. 0 to 5 phr, particularly preferably 0.5 to 3 phr, very particularly preferably 1 to 2 phr.
[0148] Of the components listed under i. to v., it is particularly preferred that only components iii, iv. and v. or iii. and v. are present as further components, preferably in the abovementioned particularly preferred and / or more particularly preferred amounts.
[0149] Vulcanizable rubber composition
[0150] The vulcanizable rubber composition of the present invention comprises the rubber composition of the present invention and a vulcanization system for vulcanization thereof.
[0151] Vulcanization system
[0152] The vulcanization system is not contained in the rubber composition of the invention here, but is regarded as an additional system regulating its crosslinking. By adding the vulcanization system to the rubber composition of the invention, a vulcanizable rubber composition of the invention is obtained.
[0153] The rubber composition of the present invention based on halogenated butyl rubber can be used with a variety of different vulcanization systems. Chlorine-carbon bonds, which are weaker than carbon-carbon bonds, but especially bromine-carbon bonds, can be vulcanized faster and better co-vulcanized with general-purpose rubbers.
[0154] The vulcanization of the rubber composition of the present invention is preferably carried out using zinc oxide and / or sulfur.
[0155] In the preferred variants described below, zinc oxide is preferably used in combination with various organic compounds for vulcanization. By means of various additives, the vulcanization behavior and thus the properties of the vulcanizate obtained can be influenced.
[0156] In the first variant of the vulcanization based on zinc oxide, it is preferred to add small amounts of saturated fatty acids having 12 to 24, preferably 14 to 20 and particularly preferably 16 to 18 carbon atoms, such as stearic acid and / or zinc stearate, to the zinc oxide as vulcanization accelerators. This can increase the vulcanization rate. However, the use of the above-mentioned fatty acids in most cases reduces the final grade of the vulcanization.
[0157] In a second variant of the zinc oxide-based vulcanization, so-called thiurams such as thiuram monosulfide and thiuram disulfide, and / or dithiocarbamates are added to zinc oxide in the absence of sulfur to shorten the scorch time and improve the vulcanization efficiency by forming a particularly stable network.
[0158] In a third variant of zinc oxide-based vulcanization, alkylphenol disulfide is added to the zinc oxide to adapt the scorch time, in particular to accelerate the scorch time.
[0159] In another variant of the zinc oxide-based vulcanization, the fourth variant, zinc oxide is used in combination with polymethylolphenol resins and their halogenated derivatives, wherein neither sulfur nor sulfur-containing compounds are used.
[0160] In another kind of, the fifth variant of the vulcanization based on zinc oxide, vulcanization is carried out by the combination of zinc oxide and thiazole and / or sulfenamide and preferably sulphur.Thiazole and sulfenamide are preferably selected from the group consisting of 2-mercaptobenzothiazole (MBT), mercaptobenzothiazole disulfide (MBTS), N-cyclohexyl-2-benzothiazole sulfenamide (CBS), 2-morpholinyl-thiobenzothiazole (MBS) and N-tert-butyl-2-benzothiazole sulfenamide (TBBS).Adding sulphur to such systems can improve vulcanization rate and degree of vulcanization, and contribute to the processability of rubber components in the vulcanization process.It is also advantageous to carry out co-vulcanization with the rubber (especially the above-mentioned rubber) that is different from halogenated butyl rubber.The use of this vulcanization system preferably provides heat-resistant and fatigue-resistant vulcanized materials, even if it can also show good adhesion with other components of vehicle tires, especially the rubber composition of carcass in vulcanized state. Particularly advantageous vulcanization systems comprise zinc oxide, thiazoles, such as preferably mercaptobenzothiazole disulfide (MBTS), and sulfur. Particularly preferred is the combination of the first variant with the fifth variant, i.e. the use of a vulcanization system comprising zinc oxide, thiazoles, such as preferably mercaptobenzothiazole disulfide (MBTS), sulfur and stearic acid and / or optionally zinc stearate.
[0161] Less preferred vulcanization systems are based on pure sulfur vulcanization or peroxide vulcanization, the latter of which may result in an undesirable reduction in molecular weight due to cleavage of the molecules, especially when butyl or other rubbers are also used.
[0162] In the context of the present invention, the vulcanization of the rubber composition of the present invention is carried out in the presence of a specific filler F1 (preferably a specific HTC lignin). The excellent properties of the vulcanized rubber composition of the present invention, in particular its suitability as an inner liner, are essentially based on the combination of a suitable rubber component with a specific filler F1 (in particular the preferred HTC lignin) and a zinc oxide-based vulcanization system (preferably the vulcanization system referred to above as the fifth variant, even more preferably a combination of the first variant and the fifth variant).
[0163] Individual components of the vulcanization system which are not able to initiate vulcanization by themselves may also be contained in the rubber composition of the invention as "other components of the rubber composition". Thus, in particular, stearic acid and / or optionally zinc stearate and / or thiazole compounds may already be present in the rubber composition and the complete vulcanization system may be formed by in situ addition of zinc oxide and sulfur.
[0164] Set
[0165] Due to the relationship between rubber composition of the present invention and the cross-linking system selected for its vulcanization, the invention further relates to a kit, which comprises rubber composition of the present invention and vulcanization system (preferably zinc oxide and / or sulfur-based vulcanization system). In the kit, rubber composition of the present invention and vulcanization system are spatially separated from each other, and therefore can be stored. The kit is used to prepare a vulcanizable rubber composition. For example, the rubber composition of the present invention constituting a part of the kit can be used as the following part (A) in the step 1 of the method for preparing a vulcanizable rubber compound, and the second part of the kit, i.e. the vulcanization system, can be used as the part (B) in the step 2 of the method.
[0166] Preferably, the kit comprises:
[0167] The rubber composition of the present invention as part (A), and
[0168] A vulcanization system comprising zinc oxide and / or sulfur as part (B).
[0169] Particularly preferably, the kit comprises:
[0170] The rubber composition of the present invention as part (A), and
[0171] A vulcanization system comprising zinc oxide, sulfur and thiazole as part (B); or
[0172] The rubber composition of the present invention comprises thiazole as part (A), and
[0173] A vulcanization system comprising zinc oxide and / or sulfur as part (B).
[0174] More particularly preferably, the kit comprises:
[0175] The rubber composition of the present invention as part (A), and
[0176] a vulcanization system comprising zinc oxide, sulfur, thiazole and stearic acid and optionally zinc stearate as part (B); or
[0177] a rubber composition of the invention comprising stearic acid and optionally zinc stearate as part (A), and
[0178] A vulcanization system comprising zinc oxide, sulfur and thiazole as part (B).
[0179] The preferred thiazole in the above kit is MBTS.
[0180] In contrast to a vulcanizable rubber composition which already comprises the constituents of the rubber composition of the invention and the constituents of the associated vulcanization system in a homogeneous mixture, so that the vulcanizable rubber composition can be vulcanized directly, the rubber composition of the invention and the vulcanization system are spatially separated in the kit.
[0181] The vulcanizable rubber composition obtainable from the kit will also be referred to herein as the “green compound.” It can be obtained by a two-stage process as described in the following section.
[0182] Rubber composition of the present invention and method for preparing vulcanizable rubber composition produced therefrom
[0183] The preparation of the vulcanizable rubber compound is preferably carried out in two stages.
[0184] In the first stage, the rubber composition of the present invention is first prepared as a base compound (masterbatch) by compounding the components of the rubber composition. In the second stage, the components of the vulcanization system are mixed.
[0185] Phase 1
[0186] Preferably, halogenated butyl rubber and any additional rubber used optionally, and any adhesion enhancing resin used optionally are provided. However, the latter can also be added together with other additives. Preferably, the rubber has at least room temperature (23° C.), or is used after preheating to a temperature not exceeding 50° C., preferably not exceeding 45° C., particularly preferably not exceeding 40° C. It is particularly preferred that the rubber is pre-kneaded for a short time before the other ingredients are added. If an inhibitor (such as magnesium oxide) is used for subsequent vulcanization control, it is preferably also added at this time.
[0187] Subsequently, the filler F1 to be used according to the invention, preferably HTC lignin, and optionally other fillers, preferably with the exception of zinc oxide, are added, since zinc oxide is used as a component of the vulcanization system in the rubber composition according to the invention and is therefore not considered a filler herein. The addition of the filler F1 to be used according to the invention, preferably HTC lignin, and optionally other fillers is preferably carried out in increments.
[0188] Advantageously, but not necessarily, the softener and other ingredients, such as stearic acid and / or zinc stearate, are added only after the addition of the filler F1 to be used according to the invention, preferably HTC lignin, or other fillers, if used. This facilitates the incorporation of the filler F1 to be used according to the invention, preferably HTC lignin, and other fillers, if present. However, it is advantageous to incorporate a portion of the filler F1 to be used according to the invention, preferably HTC lignin, or other fillers, if present, with the softener and any other ingredients optionally used.
[0189] The maximum temperature obtained during the first stage preparation of the rubber composition ("dumping temperature") should not exceed 140°C, because above these temperatures there is a risk of partial decomposition of the reactive halogenated butyl rubber. Preferably, the maximum temperature during the first stage preparation of the rubber composition is from 100°C to 130°C, particularly preferably from 105°C to 120°C.
[0190] The mixing of each component of the rubber composition of the present invention is usually carried out by an internal mixer equipped with a tangential or meshing (i.e., intermeshing) rotor. The latter usually allows better temperature control. However, for example, a double-roll mixer can also be used to mix.
[0191] After the rubber composition is prepared, it is preferably cooled before proceeding to the second stage. This type of process is also called ripening. The typical ripening period is 6 to 24 hours, preferably 12 to 24 hours.
[0192] Phase 2
[0193] In the second stage, the components of the vulcanization system are mixed into the rubber composition of the first stage, thereby obtaining the vulcanizable rubber composition of the present invention.
[0194] If a vulcanization system based on zinc oxide is used as the vulcanization system, zinc oxide and other components, such as in particular sulfur and particularly preferably thiazole, are added in a second stage.
[0195] The maximum temperature ("dump temperature") obtained during the preparation of the mixture of the vulcanization system and the rubber composition in the second stage should preferably not exceed 110° C., particularly preferably not exceed 105° C. The preferred temperature range is 90° C. to 110° C., particularly preferably 95° C. to 105° C. At temperatures exceeding 105° C. to 110° C., premature vulcanization may occur.
[0196] After mixing the vulcanization system in the second stage, the composition is preferably cooled.
[0197] Therefore, in the above two-stage process, the rubber composition of the present invention is first obtained in the first stage, which is supplemented in the second stage to form a vulcanizable rubber composition, in particular a vulcanizable rubber composition for an inner liner.
[0198] Method for further processing of the vulcanizable rubber composition of the invention
[0199] The vulcanizable rubber composition obtained in the above-described two-stage process is preferably further processed by calendering, extrusion or in a roll head process.
[0200] Calendering
[0201] The vulcanizable rubber composition of the present invention is preferably fed to a calender in the first step (a), for example, using a preheating mill and a downstream feeder mill, or fed during extrusion using an extruder. In both cases, the temperature of the vulcanizable rubber composition before it is fed to the calender should preferably be 65° C. to 85° C., particularly preferably 70° C. to 80° C.
[0202] In the second step (b), calendering is carried out, wherein different roll positions of preferably three or four rolls of the calender are possible. Preferably, calendering is carried out with a four-roller Z-calender ("inclined Z-calender") or a four-roller L-calender ("inverted L-calender"). Here, the cooler pick-up roll preferably has a temperature of 75° C. to 85° C., while the hotter roll preferably has a temperature of 85° C. to 95° C.
[0203] After calendering, the calendered vulcanizable rubber composition leaves the calender as a calender web in a third step (c) and is cooled, preferably to a temperature below 35° C., before subsequent processing. It is also possible to consolidate several calender webs into multiple layers when the calender web leaves the calender. Care must be taken to ensure that no unwanted air inclusions occur during consolidation.
[0204] After these three steps, the calendered web or the calendered web consolidated into multiple layers is advantageously stored in a fourth step (d) for at least 3 hours, even better for at least 4 hours, preferably at least 12 hours to 24 hours. This storage is for complete cooling of the calendered web and for stress relaxation.
[0205] The calendering is preferably carried out at a calendering speed of 20 m / min to 35 m / min, particularly preferably 25 m / min to 30 m / min.
[0206] Extrusion
[0207] In addition to calendering, linings can also be obtained by extrusion.
[0208] Preferably, in the first step (a), the vulcanizable rubber composition of the present invention is fed into an extruder, for example, by a two-roll mixer or other suitable feeding device. Here, before the vulcanizable rubber composition is fed into the calender, its temperature should preferably be 65° C. to 85° C., particularly preferably 70° C. to 80° C.
[0209] In the second step (b) of extrusion, temperatures of 100° C. may be achieved. Therefore, special care must be taken to ensure that scorching does not occur.
[0210] After extrusion, the extruded vulcanizable rubber composition leaves the extruder as a web in a third step (c) and is cooled, preferably to below 35° C., before subsequent processing. Multiple webs may also be consolidated into multiple layers as the web leaves the extruder. Care must be taken to ensure that no unwanted air inclusions occur during consolidation.
[0211] After these three steps, the web or the web consolidated into multiple layers is advantageously stored in a fourth step (d) for at least 3 hours, even better for at least 4 hours, preferably at least 12 hours to 24 hours. This storage is for complete cooling of the web and for stress relaxation.
[0212] Roller head process
[0213] In the roller head process, in contrast to the multi-roll calendering described above, the rubber compound from an extruder with a preformed head is fed into the calendering nip of a two-roll or three-roll calender. The extruder itself can be supplied with hot or cold feed. For example, a cold-feed pin extruder can be used. When the provided compound matches the web to be calendered in thickness and width, the roller gap (calendering nip) can optimize the feed, which can be achieved by selecting a preformed head and a replaceable forming die mounted at its end.
[0214] In terms of operating performance, the roller head line is located between the extruder and the calender, where uniform flow in the extruder die is critical to quality and size when producing thicker webs, while the calendering behavior is more important for thinner webs.
[0215] The operating temperature is within the calendering and extrusion temperature range of the above processes.
[0216] As previously mentioned with respect to calendering, the finished web must be cooled after leaving the calender according to step (c) above, and preferably prior to step (d) above.
[0217] The vulcanized webs obtained by calendaring, extrusion or by the roll head process have a layer thickness of 0.3 mm to 5 mm, particularly preferably 0.4 mm to 4 mm, very particularly preferably 0.5 mm to 3 mm. These layer thickness ranges are typical thickness ranges for inner liners.
[0218] Vulcanized rubber composition
[0219] Another object of the invention is a vulcanized rubber composition obtainable from the above-described vulcanizable rubber composition, for example also by using a kit.
[0220] The vulcanization conditions depend on the vulcanization system used. The suitable vulcanization temperature is preferably 140°C to 200°C, particularly preferably 150°C to 180°C.
[0221] Preferably, the vulcanized rubber composition is an inner liner of a pneumatic tire.
[0222] Properties of vulcanized rubber compositions
[0223] The vulcanized rubber composition obtained from the vulcanizable rubber composition of the present invention preferably has:
[0224] (a) a Shore A hardness of greater than 50 to less than 70, particularly preferably 52 to 65, more particularly preferably 54 to 62; and / or
[0225] (b) a modulus 300 of 3.8 MPa to 10 MPa, particularly preferably 4.5 MPa to 9 MPa, more particularly preferably 5.5 MPa to 8.5 MPa; and / or
[0226] (c)0.950g / cm 3 Up to 1.120g / cm 3 , particularly preferably 0.980 g / cm 3 Up to 1.110g / cm 3 , more preferably 1.050 g / cm 3 Up to 1.100g / cm 3 density; and / or
[0227] (d) Less than 3.9×10 -17 m 2 / Pas gas permeability, particularly preferably 3.0×10 -17 m 2 / Pas to 3.8×10 - 17 m 2 / Pas, more preferably 3.2×10 -17 m 2 / Pas to 3.7×10 -17 m 2 / Pas, for example 3.2×10 -17 m 2 / Pas to 3.5×10 -17 m 2 / Pas gas permeability.
[0228] In general, higher contents of fillers F1 which can be used according to the invention, in particular HTC lignin and optionally other fillers, generally reduce the gas permeability further, but at the expense of the tear strength and tear elongation of the composite.
[0229] Method for producing a pneumatic tire comprising an inner liner made of the vulcanizable rubber composition of the present invention
[0230] The vulcanizable web obtainable by the above method is preferably stored in the form of a roll before use and used as an inner lining material when manufacturing a pneumatic tire. For this purpose, the web must be cut to the circumference of the cylinder, which can be achieved by using an ultrasonic knife or a heatable rotary circular knife, the latter preferably in a so-called roll-cut process.
[0231] The innerliner is typically cured under pressure and / or heat along with the tire carcass and / or other tire components.
[0232] Suitable vulcanization temperatures are preferably 140°C to 200°C, particularly preferably 150°C to 180°C.
[0233] The process can be carried out, for example, by closing the press and molding the green tire into a closed mold. For this purpose, the inner bellows (heating bellows) can be pressurized with low pressure (<0.2 bar) so that the bellows can also be fitted into the green tire. Afterwards, the press and mold are completely closed. The pressure in the bellows increases (to the molding pressure, typically about 1.8 bar). As a result, the profile is imprinted on the tread, as well as the sidewall label. In the next processing step, the press is locked and the clamping force is applied. The clamping force varies depending on the type of press and the size of the tire and can reach up to 2500 kN using hydraulic cylinders. After the closing force has been applied, the actual vulcanization process begins. Here, the mold is continuously heated by external steam, where the temperature is usually set at 150°C to 180°C. For the internal medium, there are many different variants depending on the type of tire. For example, steam or hot water is used in the heating bellows. Depending on the type of tire, such as passenger car or truck tires, the internal pressure may vary and be different.
[0234] All measured quantities related to the present invention mentioned in this specification were determined according to the procedures mentioned in the experimental part.
[0235] Use of filler F1 to be used according to the invention, in particular HTC lignin
[0236] Another object of the present application is the use of filler F1 as defined above with respect to the rubber composition of the invention, preferably HTC lignin, as filler for the preparation of a rubber composition for innerliners, in particular pneumatic tire innerliners, in particular vehicle pneumatic tire innerliners.
[0237] The invention is illustrated below with reference to several examples.
[0238] Example
[0239] Various testing procedures were performed on the components of the rubber composition, the unvulcanized rubber composition, and the vulcanized rubber composition, as will be described in more detail below.
[0240] Characterization of fillers (HTC lignin or carbon black)
[0241] Mass-related surfaces (BET surfaces and STSA surfaces)
[0242] The specific surface area of HTC lignin was determined by nitrogen adsorption according to the ASTM D 6556 (2019-01-01) standard provided for industrial carbon black. According to this standard, the BET surface area (total specific surface area according to Brunauer, Emmett and Teller) and the external surface area (STSA surface area; statistical thickness surface area) are determined as follows.
[0243] Before the measurement, the sample to be analyzed is dried at 105 ° C to a dry matter content ≥ 97.5% by weight. In addition, the measuring cell is dried in a drying cabinet at 105 ° C for several hours and then weighed in the sample. The sample is then filled into the measuring cell using a funnel. In case the axis of the upper measuring cell becomes contaminated during the filling process, it is cleaned using a suitable brush or pipe cleaner. In the case of strongly flying dust (static electricity) materials, glass wool is additionally weighed in the sample. The glass wool serves to retain any material that may fly up during the baking process and contaminate the device.
[0244] The samples to be analyzed were baked at 150°C for 2 hours, and the Al2O3 standards were baked at 350°C for 1 hour.
[0245] Depending on the pressure range, the following N2 doses were used for the determination:
[0246] p / p0=0~0.01:N2 dosage:5ml / g
[0247] p / p0=0.01~0.5:N2 dose:4ml / g
[0248] For the determination of BET, extrapolation was performed in the range of p / p0=0.05 to 0.3 with at least 6 measurement points. For the determination of STSA, extrapolation was performed in the range of the adsorbed N2 layer thickness from t=0.4 to 0.63 nm (corresponding to p / p0=0.2 to 0.5) with at least 7 measurement points.
[0249] Determination of ash content
[0250] According to DIN 51719, the anhydrous ash content of the sample is determined by thermogravimetric analysis as follows. Before weighing, the sample is ground or pulverized. Before determining the ash content, the dry matter content of the weighed material is determined. The sample material is weighed in a crucible to the nearest 0.1 mg. The furnace (including the sample) is heated to a target temperature of 815°C at a heating rate of 9°K / min and then maintained at this temperature for 2 hours. The furnace is then cooled to 300°C before removing the sample. The sample is cooled to ambient temperature in a desiccator and weighed again. The remaining ash is related to the initial weight, thereby determining the weight percentage of ash. Three measurements are performed on each sample and the average value is reported.
[0251] Determine pH
[0252] As described below, pH is determined in accordance with ASTM D 1512. If the dry sample is not already in powder form, it is ground or ground into powder. In each case, 5 g of sample and 50 g of completely deionized water are weighed in a glass beaker. The suspension is heated to a temperature of 60 ° C, a magnetic stirrer with a heating function and a stirring flea is used for constant stirring, and the temperature is maintained at 60 ° C for 30 minutes. Subsequently, the heating function of the stirrer is deactivated so that the mixture cools while stirring. After cooling, the evaporated water is replenished by adding completely deionized water again and stirred again for 5 minutes. The pH value of the suspension is determined with a calibrated measuring instrument. The temperature of the suspension should be 23 ° C (± 0.5 ° C). Each sample is measured repeatedly and the average value is reported.
[0253] Determination of heat loss
[0254] The heat loss of the sample is determined in accordance with ASTM D 1509, as described below. For this purpose, an MA100 hygrometer balance from Sartorius is heated to a drying temperature of 125°C. If the dry sample is not already in powdered form, it is ground or pulverized into a powder. Approximately 2 g of the sample to be measured are weighed on a suitable aluminum pan in the hygrometer balance and the measurement is started. As soon as the sample weight does not change by more than 1 mg within 30 seconds, this weight is considered constant and the measurement is terminated. The heat loss then corresponds to the moisture content of the sample displayed in % by weight. At least one replicate is determined for each sample. The weighted average is reported.
[0255] Determination of bulk density
[0256] The bulk density of the sample is determined according to ISO 697 as described below. A standard beaker (for determining bulk density) according to DIN ISO 60 (100 ml volume) is placed in a dish to collect the overflow. Fill the beaker with a funnel and a spatula until it overflows. Use the straight edge of the spatula to scrape off the excess along the edge of the beaker. Wipe the outside of the beaker with a dry cloth and then weigh with an accuracy of 0.1 g.
[0257] Determination of available acidic hydroxyl groups on the surface (OH group density)
[0258] According to Sipponen, the available acidic hydroxyl groups on the surface are determined qualitatively and quantitatively by colorimetry. The method according to Sipponen is based on the adsorption of the basic dye Azure B on the available acidic hydroxyl groups on the filler surface and is described in more detail in the paper "Determination of surface-accessible acidic hydroxyls and surface area of lignin by cation dye adsorption" (Bioresource Technology 169 (2014) 80-87). The amount of surface available acidic hydroxyl groups is expressed in mmol / g filler. Regardless of how the filler is obtained, the process is not only applicable to lignin-based fillers, for example, but also to the comparative carbon black N660.
[0259] Determination 14 C content
[0260] Radiocarbon dating possible according to DIN EN 16640:2017-08 14 C content (biobased carbon content).
[0261] Determination of carbon content
[0262] The carbon content can be determined by elemental analysis according to DIN 51732:2014-7.
[0263] Determination of oxygen content
[0264] The oxygen content can be determined by high temperature pyrolysis using the EuroEA3000 CHNS-O analyzer from EuroVector SpA.
[0265] Characterization of vulcanizable rubber compositions ("green compounds")
[0266] Determination of reaction kinetics / vulcanization kinetics
[0267] The time course of torque [dNm] was determined according to DIN 53529Tl 3 (torsion shear rotorless vulcanizer), and the reaction kinetics of non-vulcanized rubber compound ("green rubber compound") was determined using MDR3000Professional rheometer (MonTech Werkstoffprüfmaschinen GmbH, Buchen, Germany). The upper and lower rotating plates of the rheometer were heated to 160 ° C. 5.5g ± 0.5g of non-vulcanized rubber composition was cut from the center of the plate with scissors. Here, it is important to ensure that the cutout represents a square area and that the diagonal of the area corresponds to the diameter of the rheometer rotor. Before the non-vulcanized rubber composition is placed on the rheometer rotor, the top and bottom of the cutout are covered with a film. After inserting the non-vulcanized sample, the measurement is started immediately.
[0268] The minimum and maximum torques (M) were determined from the measured curves during a 30-minute test period at 160°C (0.5° arc, 1.67 Hz). L , M H ), and calculate the difference Δ(M H -M L ).
[0269] In addition, for each measurement curve, the minimum torque M L Defined as the maximum torque M H 0%, maximum torque M H Normalized to 100%. Then, determine the minimum torque M L The starting torque reaches the maximum torque M H The time periods are designated as T2, T 10 、T 50 and T 90 .
[0270] Characterization of vulcanized rubber compositions
[0271] Determination of Shore A hardness
[0272] The digital Shore durometer of Sauter GmbH company is used to measure the Shore A hardness of the vulcanized rubber composition according to ISO 7619-1. Before each measurement, the instrument is calibrated using the calibration plate provided. In order to measure the hardness, three S2 bars for tensile test are stacked on each other according to DIN53504 perforation. Hardness measurement is carried out at five different positions on the stack. The Shore A hardness of the vulcanized rubber composition represents the mean value of five measurements. Between vulcanization and the test, the sample is stored at room temperature for at least 16 hours in the laboratory.
[0273] Determination of the density of vulcanized rubber compositions
[0274] The density of the vulcanized rubber composition was determined according to DIN EN ISO 1183-1:2018-04 (method for determination of density of non-foamed plastics) method A (immersion method). Ethanol was used as the immersion medium. The density of the vulcanized rubber composition represents the average of three determinations. Between vulcanization and testing, the samples were stored in the laboratory at room temperature for at least 16 hours.
[0275] Determination of gas permeability
[0276] The permeability of the vulcanized rubber compositions to air is determined according to ISO 15105. The measurements are carried out at 70° C. The gas permeability represents the average of three measurements. Between vulcanization and testing, the samples are stored in the laboratory at room temperature for at least 16 hours.
[0277] Determination of tear strength, tear elongation and stress value (modulus)
[0278] Tensile testing is used to determine tear strength, tear elongation and stress values of non-preloaded specimens. In a tensile test, the specimen is stretched at a constant strain rate until it tears, and the required force and length change are recorded.
[0279] Tear strength: The tear strength σR is the quotient of the force FR measured at the moment of tearing and the initial cross-section A0 of the sample body.
[0280] Tensile strength: The tensile strength σmax is the quotient of the maximum force Fmax measured and the initial cross-section A0 of the sample body. For elastomers, the force FR generated during tearing is usually also the maximum force Fmax.
[0281] Tearing elongation: Tearing elongation εR is the quotient of the length change LR-L0 measured at the moment of tearing and the length L0 of the sample body measured initially. It is expressed as a percentage. For the sample strip used, L0 is the specified distance between the two measuring marks.
[0282] Stress value: The stress value σi is the tensile force Fi that occurs when a certain elongation is reached, related to the initial cross-section A0. For the sample strip, the strain is related to the initially measured length L0, i.e. the specified distance between the measuring marks.
[0283] The tensile strength, tear elongation and stress values of the vulcanized rubber compositions were determined using a test instrument of the Tensor Check type from Gibitre Instruments according to ISO 37. Between vulcanization and testing, the samples were stored in the laboratory at room temperature for at least 16 hours. To determine the modulus, at least five dumbbell specimens were punched out of the vulcanized rubber composition, the specimen dimensions being as per ISO 37 (bar type S2). The thickness of the specimen body was determined using The crosshead speed during the tensile test was 200 mm / min. The specified measured values for tensile strength, elongation at break and stress values (modulus 100, 200, 300) are the average of five measurements.
[0284] Preparation Example
[0285] Preparation of HTC lignin usable in the present invention
[0286] Two HTC lignins with different properties, in particular different BET and STSA surface areas and OH group densities, were prepared. The preparation of HTC lignins A and B was similar to the HCT lignin described in WO 2017 / 085278.
[0287] Both HTC lignins A and B were characterized as shown in Table 1. The characterization results were compared with commercially available and ASTM standardized industrial carbon black (type N660) available from Lehmann and Voss.
[0288] Table 1
[0289] test unit HTC Lignin A HTC Lignin B Carbon Black N660 STSA <![CDATA[m 2 / g]]> 22 40 35 BET <![CDATA[m 2 / g]]> 23 39 34 Ash content weight% 3.8 3.1 0.30 pH . / . 8.1 7.9 9.1 Heat loss weight% 1.5 2.4 0.7 density <![CDATA[g / cm 3 ]]> 1.35 1.35 1.82 <![CDATA[ 14 C content]]> Bq / g C 0.244 0.243 ≤0.05 Carbon content weight% 71 71 >98 Oxygen content weight% 22 22 <0.5 <![CDATA[OH group 1 density]]> mmol / g 0.3 0.34 0
[0290] 1 = available acidic hydroxyl groups on the surface
[0291] Preparation of different rubber compositions (stage 1)
[0292] In a Haake Rheomix 3000 S mixer (from ThermoFisher) equipped with a Banbury rotor, the rubber composition (base compound; masterbatch) was prepared as follows, the ingredients and amounts are given in Table 2.
[0293] Before the start of mixing, the mixing chamber was heated to 40° C. The amounts of the individual components were calculated in each case to give a mixing chamber with a filling level of 70%. All components were pre-weighed on a balance from the company Kern. After starting the rotor (50 rpm), the mixing chamber was filled with rubber, the filling device leading to the mixing chamber was pneumatically locked, and mixing was carried out to a total mixing time of 1 minute. Thereafter, the filling device of the mixing chamber was opened, 1 / 3 of the filler amount was added, the mixing chamber was closed again, and mixing was carried out to a total mixing time of 2 minutes. The filling of the mixing chamber was then opened, 1 / 6 of the filler amount was added, then 1 / 2 of the oil amount, then 1 / 6 of the filler amount was added, the mixing chamber was closed again, and mixing was carried out to a total mixing time of 4 minutes. Thereafter, the filling device of the mixing chamber was opened, 1 / 6 of the filler amount, then 1 / 2 of the oil amount, then 1 / 6 of the filler amount and additives were added, the mixing chamber was closed again, and mixing was carried out to a total mixing time of 6 minutes. After a total mixing time of 6 and 8 minutes, respectively, the mixing chamber was aerated. The ejection temperature was controlled by adjusting the speed. Ejection occurred after a total mixing time of 10 minutes and the temperature of the composite was measured.
[0294] After the mixing process, the compound is removed from the mixer, cooled and homogenized on a laboratory mill with a medium roll gap width. To this end, the compound is first passed through the roll gap once, the resulting composite sheet is rolled into a "doll" and punched through the roll gap six times from the top. The sheet is then cooled on a cooling table until the sheet reaches room temperature.
[0295] Table 2
[0296]
[0297] 1 Bromobutyl X-Butyl BB 2230 from Arlanxeo
[0298] 2 Carbon Black N660 from Lehmann und Voss
[0299] 3 Paraffin oil from Hansen und Rosenthal
[0300] 4 The highest temperature reached during mixing ("purge temperature")
[0301] Comparative Example V1 differs from Examples B1 to B4 of the present invention in that industrial carbon black N660 is used in this comparative example. In Examples B1 and B3 of the present invention, the amount of HTC lignin used is equal in volume relative to carbon black N660. In Examples B2 and B4, the amount of HTC lignin used is equal in weight relative to carbon black N660.
[0302] Preparation of vulcanizable rubber composition (stage 2)
[0303] Vulcanizable "green compounds" of inventive examples B1 to B4 were prepared for each rubber composition by mixing a vulcanization system consisting of 5 phr zinc oxide, 1.5 phr sulfur and 1.25 phr mercaptobenzothiazole disulfide (MBTS) (phr = parts by weight based on 100 parts by weight of rubber mass). In comparative example V1, zinc oxide had been added in step 1.
[0304] First, the cooled composite sheet is cut into strips and the vulcanizing chemicals are weighed. After starting the rotor (50 rpm) at a mixing chamber temperature of 40°C, the sheet is fed into the mixing chamber, the filling device leading to the mixing chamber is pneumatically locked, and mixing is performed until the total mixing time reaches 2 minutes. Subsequently, the filling device leading to the mixing chamber is opened, the vulcanizing chemicals are added, the filling device leading to the mixing chamber is pneumatically locked, and mixing is performed until the total mixing time reaches 5 minutes. The ejection temperature is controlled by adjusting the speed. Ejection occurs after a total mixing time of 5 minutes and the temperature of the composite is measured.
[0305] After the mixing process, the compound is removed from the mixer, cooled and homogenized on a laboratory mill with a medium roll gap width. To this end, the compound is first passed through the roll gap once, the resulting composite sheet is rolled into a "doll" and punched through the roll gap six times from the top. The sheet is then cooled on a cooling table until the sheet reaches room temperature.
[0306] This gives a vulcanizable composition V1 g and B1 g To B4 g , where "g" stands for "green compound" and the remaining names correspond to Examples V1 and B1 to B4.
[0307] Preparation of vulcanized rubber compositions
[0308] The vulcanizable rubber composition V1 g and B1 g To B4 g , by vulcanizing at 160°C in a vulcanizing press, a fully vulcanized sample V1 was obtained v and B1 v To B4 v , corresponding to the vulcanizable green compound V1 g and B1 g To B4 g. The composite sheet is rolled to a thickness of 3 mm without wrinkles by continuously reducing the roller gap of the laboratory roller. A square piece with the dimensions of 250x250 mm is then cut from the sheet with scissors and transferred to the press (Gibitre Instruments SRL vulcanizing press with built-in mold for 2 mm thick test plates). The vulcanization time to be set comes from the t90 time determined in the rheometer test plus one minute per millimeter of sheet thickness (i.e. two minutes when using a 2 mm frame). After the pressing time has elapsed, the vulcanized rubber mat is immediately removed. The mat is placed on a cooling table to cool. After cooling, the protruding edges are carefully cut off with scissors.
[0309] Test results
[0310] Table 3 reports the vulcanizable rubber composition V1 g and B1 g To B4 g Test results of reaction kinetics / vulcanization kinetics.
[0311] Table 3
[0312] Measured variables unit <![CDATA[V1 g ]]> <![CDATA[B1 g ]]> <![CDATA[B2 g ]]> <![CDATA[B3 g ]]> <![CDATA[B4 g ]]> <![CDATA[M L ]]> dN 2.0 1.7 2.2 2.0 2.7 <![CDATA[M n ]]> dN 9.8 7.1 9.9 8.6 11.3 <![CDATA[Δ(M H -M L )]]> dN 7.8 5.5 7.7 6.6 8.6 <![CDATA[T2]]> minute 0.8 1.1 1.1 1.1 1.1 <![CDATA[T 10 ]]> minute 2.00 3.26 2.95 2.68 2.49 <![CDATA[T 50 ]]> minute 4.11 12.35 11.30 12.0 12.2 <![CDATA[T 90 ]]> minute 14.3 24.1 23.0 25.1 25.4
[0313] As can be seen from Table 3, complex B1 g To B4 g The scorching is delayed, thus improving the processability. The full cure time is significantly extended. This is not a disadvantage when used in linings, since the component is directly exposed to the temperature emitted by the heated bellows, which allows full cure. However, the reaction kinetics can be accelerated accordingly by using zinc stearate (1phr to 2phr). However, the dosage of zinc oxide must be adjusted.
[0314] Table 4 shows the measured values obtained for the vulcanized test specimens.
[0315] Table 4
[0316]
[0317] As can be seen in Table 4, good levels of physical property values can be achieved when using HTC lignin. The reinforcement properties show a reinforcement index at the level of the reference composites, which index depends on the degree of filling (same weight dosage or same volume dosage). The modulus can be adjusted according to the BET surface area and dosage, allowing specific optimization of various physical properties. Regardless of these adjustments, B1 v To B4 v The density of the composite is significantly reduced. As long as the amount of HTC lignin is greater than the "equal volume", the gas permeability is also improved. Therefore, HTC lignin can adjust low density, low permeability, high elongation at break and good crack resistance. Here, Example B1v (BET=20m 2 / g of HTC lignin) shows a combination of low density, high elongation at break and reduced gas permeability.
Claims
1. A rubber composition, comprising: a rubber component comprising at least one halogenated butyl rubber selected from the group consisting of bromobutyl rubber and chlorobutyl rubber, A filler component, the filler component comprising at least one filler F1, the filler F1 being a lignin-based filler, and the filler F1 having: According to DIN EN 16640:2017-08, the 14 The C content is in the range of 0.20 Bq / g carbon to 0.45 Bq / g carbon; The carbon content determined by elemental analysis according to DIN 51732:2014-7 is in the range of 60% to 85% by weight relative to the ash-free and water-free filler; According to ASTM D 6556-2019, the STSA surface area measured by nitrogen adsorption is 10 m 2 / g filler up to 50 m 2 / g filler range; The oxygen content determined by high temperature pyrolysis is in the range of 15% to 30% by weight relative to the ash-free and water-free filler; and having acidic hydroxyl groups on its surface, and the amount of acidic hydroxyl groups available on the surface according to Sipponen is in the range of 0.05 mmol / g to 40 mmol / g; And among them, The proportion of halogenated butyl rubber in the rubber composition is 70 phr to 100 phr, The rubber composition comprises 50 to 100 phr of filler F1.
2. The rubber composition according to claim 1, characterized in that The filler component comprises 50 phr to 90 phr of filler F1.
3. The rubber composition according to claim 1 or 2, characterized in that The rubber composition comprises one or more other ingredients selected from the group consisting of: i. Rubber other than halogenated butyl rubber, ii. a filler F2 different from the filler F1, iii. Softener, iv. adhesion enhancing resins, and v. Additives that promote vulcanization.
4. The rubber composition according to claim 3, characterized in that i. the rubber other than halogenated butyl rubber is selected from the group consisting of natural rubber, butyl rubber and styrene-butadiene rubber, and / or ii. the filler F2 different from the filler F1 is selected from the group consisting of carbon black and layered silicates, and / or iii. the softener is selected from the group consisting of esters of aliphatic dicarboxylic acids, paraffin oils and naphthenic oils, and / or iv. the adhesion enhancing resin is selected from the group consisting of aliphatic hydrocarbon resins, aromatic hydrocarbon resins, phenolic resins, phenol-formaldehyde resins and phenol acetylene resins; and / or v. The vulcanization-promoting additive is selected from the group consisting of saturated fatty acids having 12 to 24 carbon atoms and thiazoles.
5. The rubber composition according to claim 3, characterized in that i. the rubber other than halogenated butyl rubber is contained in the rubber composition in an amount of 0 phr to 30 phr, and / or ii. the filler F2 different from the filler F1 is contained in the rubber composition in an amount of 0 phr to 40 phr, and / or iii. the softener is contained in the rubber composition in an amount of 0 phr to 15 phr, and / or iv. the adhesion enhancing resin is contained in the rubber composition in an amount of 0 phr to 15 phr; and / or v. The vulcanization-accelerating additive is contained in the rubber composition in an amount of 0 phr to 5 phr.
6. The rubber composition according to claim 1 or 2, wherein: The filler F1 is hydrothermal carbonized lignin.
7. The rubber composition according to claim 1 or 2, wherein: The filler F1 is: The oxygen content determined by pyrolysis is in the range of 17% to 28% by weight relative to the ash-free and water-free filler; and / or The amount of available acidic hydroxyl groups on the surface according to Sipponen is in the range of 0.1 mmol / g to 30 mmol / g.
8. A vulcanizable rubber composition, comprising: The rubber composition according to any one of claims 1 to 7 and a vulcanization system comprising zinc oxide and / or sulfur.
9. The vulcanizable rubber composition according to claim 8, characterized in that The vulcanization system is selected from the group consisting of the following vulcanization systems, the vulcanization system comprising zinc oxide and a. at least one saturated fatty acid having 12 to 24 carbon atoms; b. at least one thiuram and / or dithiocarbamate; c. at least one alkylphenol disulfide; d. at least one polyhydroxymethylphenol resin or a halogenated polyhydroxymethylphenol resin; e. sulfur and at least one thiazole and / or sulfenamide; f. Sulfur, at least one thiazole and / or sulfenamide and at least one saturated fatty acid having 12 to 24 carbon atoms.
10. The vulcanizable rubber composition according to claim 9, characterized in that Vulcanization system b does not contain sulfur.
11. The vulcanizable rubber composition according to claim 9, characterized in that The vulcanization system d contains no sulfur or no sulfur-containing compounds. 12 . A kit comprising the rubber composition (A) as claimed in claim 1 and the vulcanization system (B) as defined in claim 9 in a spatially separated form.
13. A method for preparing a rubber composition as defined in any one of claims 1 to 7, characterized in that The rubber component is provided, and the filler component, and optionally a softener, an adhesion enhancing resin, and an additive to accelerate vulcanization are mixed therein.
14. A method for preparing a vulcanizable rubber composition according to any one of claims 8 to 11, characterized in that In a first stage, the rubber composition according to the process of claim 13 is prepared, and subsequently, in a second stage, the mixing of the components of the vulcanization system is carried out.
15. A method for further processing a vulcanizable rubber composition as defined in any one of claims 8 to 11, characterized in that The vulcanizable rubber composition is formed into a web by calendaring, extrusion or roller head process.
16. The method according to claim 15, characterized in that The thickness of the mesh is in the range of 0.3 mm to 5 mm.
17. A method for manufacturing a pneumatic tire, comprising the method according to claim 15 or 16, and the subsequent step of cutting the web to a size suitable for a pneumatic tire innerliner, and comprising the subsequent step of vulcanizing the innerliner thus obtained together with the pneumatic tire carcass.
18. Use of the filler F1 defined in claim 1 or 6 for preparing a rubber composition for an inner liner.
19. A vulcanized rubber composition obtainable by vulcanizing the vulcanizable rubber composition according to any one of claims 8 to 11.
20. The vulcanized rubber composition according to claim 19, wherein (a) Shore A hardness in the range of greater than 50 and less than 70 according to ISO 7619-1, and / or (b) a modulus 300 according to ISO 37 of 3.8 MPa to 10 MPa; and / or (c) Density at 23°C according to DIN EN ISO 1183-1: 2018-04: 0.950 g / cm 3 Up to 1.120 g / cm 3 ; and / or (d) The gas permeability to air at 70°C according to ISO 15105 is less than 3.9 × 10 -17 m 2 / Pas.
21. The vulcanized rubber composition according to claim 19 or 20, wherein The composition is an inner liner of a pneumatic tire.
